2018
DOI: 10.1088/1361-6404/aa9034
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and characterizing beat phenomena with a smartphone

Abstract: Nowadays, smartphones are in everyone’s life. Apart from being excellent tools for work and communication, they can also be used to perform several measurements of simple physical magnitudes, serving as a mobile and inexpensive laboratory, ideal for use physics lectures in high schools or universities. In this article, we use a smartphone to analyse the acoustic beat phenomena by using a simple experimental setup, which can complement lessons in the classroom. The beats were created by the superposition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Smartphone data was used in conjunction with an FFT data analysis in an experiment on acoustic beat phenomena in [12]. The smartphone measurement app phyphox [13] contains a tool for continuously viewing the FFT of measured acceleration data [14], and the phyphox group has listed some short example experiments on their YouTube channel [15].…”
Section: Introductionmentioning
confidence: 99%
“…Smartphone data was used in conjunction with an FFT data analysis in an experiment on acoustic beat phenomena in [12]. The smartphone measurement app phyphox [13] contains a tool for continuously viewing the FFT of measured acceleration data [14], and the phyphox group has listed some short example experiments on their YouTube channel [15].…”
Section: Introductionmentioning
confidence: 99%
“…The development of a sound experimentation tool with the help of audacity software concluded that the effect of wind speed is proportional to the speed of sound (Siti et al, 2020). Physics experiments can use a smartphone microphone as a sound wave catcher which is used as a measuring tool through an android application with a maximum accuracy value of experimental results, thus it can increase student motivation in learning (Gimenez et al, 2016;Osorio et al, 2017). Research related to the use of audacity software to conduct experiments using flutes obtained experimental results in the form of basic tone frequencies that match the concept of an open organ pipe (Maleaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones have many applications and sensors that have been developed rapidly to help physics practicum activities (Klein et al, 2014;Kuhn & Vogt, 2012;Monteiro et al, 2015;Osario et al, 2017;Parolin & Pezzi, 2015;Pili & Violanda, 2018;Zakwandi et al, 2021). Among the available applications are Phypox and the physics toolbox.…”
Section: Introductionmentioning
confidence: 99%